Learning in Different Ways: A Study of Gender-Based Learning Style Difference - Tri Windi Oktara; Yuda Syahputra (Indonesian Counselor Association (IKI), 2025)
The phenomenon of differences in learning styles between male and female is an important issue in the field of education, because it can affect the effectiveness of the learning process and academic outcomes. This study was conducted with the aim of determining whether there are differences in learning styles between male and female. The study, which was conducted using a comparative method, had 152 respondents in the late adolescent category, consisting of 34 male and 118 female. The learning style scale, developed by the researcher, demonstrated strong reliability and validity. The analysis indicated a significant difference in learning styles between genders, without reporting detailed statistical symbols in the abstract. Female students showed higher learning style scores, suggesting that they tend to adopt more adaptive and varied learning approaches. These findings highlight the need for educators to design learning strategies that accommodate gender-related differences, thereby supporting a more effective and inclusive learning environment. Furthermore, the results provide practical implications for teachers and curriculum developers in selecting instructional methods that optimize student engagement and learning outcomes.